Tổng hợp một số ,-không no đi từ các dẫn xuất axetyl cumarin - Thảo và cộng sự, Nguyễn Minh (Vietnam Journal of Chemistry, 2014)
The reaction of 2,4-dihydroxyacetophenone with ethyl acetoacetate to give 6-acetyl-5-(or 7-) hydroxy-4-methyl coumarines or 3-acetyl-7-hydroxy-4-methyl coumarine. By condensation of 6-acetyl coumarines with aromatic aldehydes have been obtained a,b-unsaturated ketones. But by analogons reaction of 3-acetyl-7-hydroxy-4-methyl coumarine with aromatic aldehydes have been prepared products of condensation in 3-acetyl group and in 4-methyl group. Structure of these products has been determined by IR, 1H-NMR and MS spectrocopies. Antimicrobial and antifungal activities of these compounds have been investigated.